Selective synthesis of α- and β-glycosides of N-acetyl galactosamine using rare earth metal triflates - Wang, Jiajia; Zhang, Wei; Cao, Wei; Liu, Kang; Su, Shihao; Ma, Jing; Li, Xia (Frontiers in Chemistry, 2022)
Structures containing galactose and GalNAc residues are specifically recognized by asialoglycoprotein receptor, allowing to selectively internalize by hepatocyte for drug targeting delivery. However, methods for direct synthesis of GalNAc glycosides are still challenge due to the poor participating group of 2-acetamido. Here, we develop a facile strategy to synthesis various GalNAc glycosides by employing a series of rare earth metal triflates, and the results demonstrate that both α-glycosides and β-glycosides of GalNAc are able to be obtained by conducting with Hf(OTf)4 and Sc(OTf)3 , respectively. These applicable results indicate that any interested GalNAc containing substrates could be prepared in this simple strategy.